Foreign exchange and money markets : managing foreign and domestic currency operations - Riehl, Heinz; Rodriguez, Rita M. (New York : McGraw-Hill, 1983)
This book is organized into three major parts. In the first part, it examines the links among participants and among different segments of each market involved to provide a basic understanding of the functioning of exchange markets and money markets. In second part, generalized knowledge developed in the first part is applied to specific problems encountered in the treasury department. While the third part, discusses the issues involved in controlling treasury operations in both exchange markets and money markets.
Rev. ed. of: Foreign exchange markets. c1977.
Includes index.
usc 09/04/18
Loans
Keywords: Foreign exchange; International finance; Money market